CRUD Application Using ReactJS Hooks - M, Kanniga Parameshwari; K, Selvi; M, Rekha; R, Karthiga (EAI endorsed transactions on internet of things, 2024)
This Project is aimed to implement CRUD operations using the library called React.js which is the advanced version of the language Javascript. The question which pops out everyone’s mind now is why React? There’s lot of open – source framework/ library/ language that is available in today’s internet. The purpose of using react is anyone with the little knowledge of javascript can easily learn react and implementation of this library is user-friendly. Also, there’s many more packages react can easily get installed in NPM and run the application whatever changes in the code can do. React also delivers good UI for the developer and to create/develop new apps for future generation. There are more than 2000 developers and over one lakh sites making use of react.js among some of the most powerful are Instagram, Netflix, Whatsapp, Uber. It also integrates with any other javascript libraries or framework and speciality of react can make changes in the web browser without doing subsequent refresh of the pages. React can allow the developer to build any complex web application and more importantly mobile application. The CRUD is an acronym for Create, Read, Update and Delete which is very much essential for implementing any strong application with relational Database. Thus, the project results in Creating the user/users with their details, read the users task, updating if any new user is created through ‘Create’ operation, and finally delete the user/users list if not wanted for an application. Though the ‘crud’ functions for creating an application can be done in any language, the author specifically uses Javascript library called react.js which is one of the best platforms to create the single page user application interfaces. The overarching goal of this application is to bring easiness for any product development company in need of crud-user functions can stick to this.